Integration of Blockchain Technology in Aircraft Maintenance Records Management: Opportunities and Challenges - Masouda Omran Salih Alfirjani (المجلة الأفروآسيوية للبحث العلمي, 2024)
The accuracy and consistency of aircraft maintenance records are vital to the aviation sector to maintain operating effectiveness and safety. Conventional record-keeping techniques are prone to inaccuracies, fraud, and inefficiency. With its immutable and decentralized ledger, blockchain technology presents a promising answer to these problems. The possibilities and difficulties of using blockchain technology in the maintenance records management system for aircraft are examined in this study. We go over the possible advantages, which include better traceability, more transparency, and improved data integrity. We also discuss the operational, legislative, and technical obstacles that need to be removed to fully utilize this integration. Our analysis shows that although blockchain technology has a lot of potential, industry stakeholders must work together and carefully evaluate several issues for it to be implemented successfully.